Communication Strategy to Survive MSMEs in The Era Of Covid Pandemic - Nurhidayati, Nurhidayati; Yani, Tri Endang; Mulyantomo, Edy; Purwantini, Sri; Santoso, Aprih (International Journal of Artificial Intelligence Research, 2022)
UMKM stands for Micro, Small and Medium Enterprises, but this small one has a very large and crucial contribution to our macro economy. MSMEs have a sizeable contribution to the Indonesian economy and contribute more than 60 percent of Gross Domestic Product (GDP). This study aims to see whether there are differences in conditions before and during the pandemic in MSMEs which include Working Hours, Size of Business, Number of Employees, Number of Buyers, and Variation. This research is also to see what strategies are used by MSMEs to survive in pandemic conditions. The sample used was 50 respondents who have businesses in food/beverage, fashion, trade, services, agriculture/livestock, handicrafts, and others. The analysis tool used is non-parametric statistics using the Wilcoxon method. The research results show that all working hypotheses are accepted. This shows that there is an effect of the Pandemic on working hours, Business Area, Number of Employees. Number of Buyers and Product Variations. To survive during a pandemic, respondents used strategies: using online media using online applications, reducing expenses, picking up the ball strategy, and replacing easily stale / damaged / expired products that are more durable